2022
DOI: 10.3390/plants11040480
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Biodiversity Assessment and Conservation of Wild Olive (Olea europaea L. subsp. europaea var. sylvestris)

Abstract: Oleaster (Olea europaea L. subsp. europaea var. sylvestris) is the ancestor of cultivated olive (Olea europaea L. subsp. europaea var. europaea) and it is spread through the whole Mediterranean Basin, showing an overlapping distribution with cultivated olive trees. Climate change and new emerging diseases are expected to severely affect the cultivations of olive in the future. Oleaster presents a higher genetic variability compared to the cultivated olive and some wild trees were found adapted to particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 93 publications
0
14
0
Order By: Relevance
“…This disease, in addition to having seriously affected the olive production of the contaminated area [ 67 ], also constitutes a serious threat to the wide biodiversity of olive, which has considerable potential that could be exploited for improving the traits of interest of this species [ 68 , 69 , 70 , 71 ]. For these reasons, interventions are needed to avoid the loss of these genetic resources [ 72 ]. The concept of a plant quarantine is part of the subject areas of plant health and plant protection, and includes national and international legislative measures and the related activities aimed to minimize the risk of the spread of pests that are harmful to the plants in a given region where they are not present, either by preventing their introduction or through eradication and containment in the case of their unintentional entry [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This disease, in addition to having seriously affected the olive production of the contaminated area [ 67 ], also constitutes a serious threat to the wide biodiversity of olive, which has considerable potential that could be exploited for improving the traits of interest of this species [ 68 , 69 , 70 , 71 ]. For these reasons, interventions are needed to avoid the loss of these genetic resources [ 72 ]. The concept of a plant quarantine is part of the subject areas of plant health and plant protection, and includes national and international legislative measures and the related activities aimed to minimize the risk of the spread of pests that are harmful to the plants in a given region where they are not present, either by preventing their introduction or through eradication and containment in the case of their unintentional entry [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…pauca [ 41 ]. Mining the available genetic resources of wild olive can allow finding interesting traits to be used in projects for favorable alleles introgression into cultivated olive to face biotic and abiotic stresses [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Olive tree (Olea europaea L.) is one of the most iconic plants in the Mediterranean Basin and across the world, having significant social, economic, and ecological impacts. The olive tree is an evergreen tree native to the Mediterranean, Asia, and Africa [7]. Many studies have shown that organic fertilizers and agricultural waste have a positive effect on olive trees.…”
Section: Introductionmentioning
confidence: 99%